2020
DOI: 10.18502/ijaai.v18i6.2176
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Guluronic Acid (G2013), As a New Anti-inflammatory Drug on Gene Expression of Pro-inflammatory and Anti-inflammatory Cytokines and Their Transcription Factors in Rheumatoid Arthritis Patients

Abstract: Rheumatoid arthritis (RA) as a long-term autoimmune disease is characterized by pain, swelling and joints destruction. The therapeutic efficacy of Guluronic acid (G2013) (patented, DEU: 102016113017.6) was reported in phase I/II clinical trial in RA patients. In this study, we aimed to evaluate the effect of G2013 as a novel non-steroidal anti-inflammatory drug (NSAID) with immunosuppressive property on genes expression of anti-inflammatory and pro-inflammatory cytokines and their transcription factors in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In agreement with previous research, our findings revealed prevalent macroscopic and microscopic indicators of arthritis (Asenso et al 2019 ; Sun et al 2021 ; Shokry et al 2022 ). TNF-α and IL-1β, as well as other pro-inflammatory cytokines produced by activated macrophages and synovial fibroblasts are major inflammatory factors in RA pathogenesis (Bakhtiari et al 2019 ; Dong et al 2020a , b ). Moreover, NLRP3-mediated caspase-1 activation plays a crucial role in osteoarthritis and RA progression ( Guo et al 2018b ; Zu et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with previous research, our findings revealed prevalent macroscopic and microscopic indicators of arthritis (Asenso et al 2019 ; Sun et al 2021 ; Shokry et al 2022 ). TNF-α and IL-1β, as well as other pro-inflammatory cytokines produced by activated macrophages and synovial fibroblasts are major inflammatory factors in RA pathogenesis (Bakhtiari et al 2019 ; Dong et al 2020a , b ). Moreover, NLRP3-mediated caspase-1 activation plays a crucial role in osteoarthritis and RA progression ( Guo et al 2018b ; Zu et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…showed that guluronic acid could reduce pro-inflammatory cytokine and their transcription factors in the blood sample of RA patients who received a dose of 500 mg twice daily for 12 weeks. They found that guluronic acid could diminish pro-inflammatory cytokines and their transcription factors and increase the anti-inflammatory cytokine and its associated transcription factor [100]. High production of pro-inflammatory factors is the cause of hyperinflammation in Nonalcoholic Steatohepatitis (NASH).…”
Section: Anti-inflammatory Effects Of Guluronic Acid and Its Molecula...mentioning
confidence: 99%
“…24,25 In several studies, the therapeutic potential of G2013 has been shown for three autoimmune diseases of ankylosing spondylitis, rheumatoid arthritis, and multiple sclerosis. 17,18,22,[26][27][28][29][30] At present, G2013 is in the first and second phases of clinical trials on ankylosing spondylitis (IRCT2016091813739N4) and rheumatoid arthritis (IRCT2016092813739N5), respectively, and in the second phase of a clinical trial on multiple sclerosis (IRCT2017042313739N8). Results of a recent study on breast cancer cell line 4T1 have shown that G2013 can inhibit cancer-related inflammation and has the potential to be used in cancer treatment.…”
Section: Introductionmentioning
confidence: 99%